2010
DOI: 10.1097/aog.0b013e3181cbc652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiplex Ligation-Dependent Probe Amplification and Karyotyping in Prenatal Diagnosis

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
1
24
2
1
Order By: Relevance
“…However, by evaluating 1550 clinical samples, we found that for aneuploidy detection, both the clinical sensitivity and specificity of our method (100%) were equivalent to QF-PCR and MLPA, which possess higher target density (Boormans et al, 2010;Papoulidis et al, 2012). Such data implied that two target loci per chromosome were sufficient for ensuring precision in prenatal diagnosis.…”
Section: Zhou Et Almentioning
confidence: 65%
“…However, by evaluating 1550 clinical samples, we found that for aneuploidy detection, both the clinical sensitivity and specificity of our method (100%) were equivalent to QF-PCR and MLPA, which possess higher target density (Boormans et al, 2010;Papoulidis et al, 2012). Such data implied that two target loci per chromosome were sufficient for ensuring precision in prenatal diagnosis.…”
Section: Zhou Et Almentioning
confidence: 65%
“…In summary, MLPA is able to detect trisomies 13, 18, 21, X and Y with comparable diagnostic accuracy [10, 29, 30] and without adverse effect on quality of life at considerably lower costs for the complete testing process. We conclude that MLPA is the preferred strategy and recommend substitution of karyotyping for MLPA for relatively low-risk indications.…”
Section: Resultsmentioning
confidence: 99%
“…ultrasound abnormalities) since these are associated with an increased risk of a chromosomal abnormality other than trisomies 13, 18, 21 and sex chromosome abnormalities. Details of the study design have been published elsewhere [9, 10]. In summary, after obtaining informed consent, amniocentesis was carried out by specifically trained obstetricians.…”
Section: Methodsmentioning
confidence: 99%
“…For pregnancies with an increased risk of Down syndrome, a change of policy from full karyotype analysis to rapid molecular aneuploidy testing would result in a failure to detect chromosome abnormalities that may have clinical consequences. This residual risk has been estimated to be 0.07% [25-27]. Next to the debate of targeted RAD replacing TK there is a discussion whether the scope of diagnostic testing should be broader than karyotyping.…”
Section: Discussionmentioning
confidence: 99%